Utilização de radiação micro-ondas para melhoria do controle de umidade de pelotas de minério de ferro - Maycon Athayde (2019)
The depleting of the world's iron ore reserves has increased the upgrading need. Currently, the most efficient agglomeration technology to enable the use of fine ore in the ironmaking is the pelletizing. However, moisture control is key to the process. The present thesis investigated the use of microwave technology for the agglomerate moisture control, through the kinetic study in bench and pilot scale drying, as well as the effect on the ore pressing process, due the strong impact of the ore particle size on the filtration. The present thesis proposes a novel kinetic mechanism for the pellets drying by means of microwaves, in bench scale. The complete drying occurred in 150 s, and the conventional method removes only 60% of the agglomerate moisture in this period. The kinetic drying phenomena at pilot scale was investigated. The new process coupling convective microwave heating had better drying than the conventional process, since the condensation regions inside the bed were completely mitigated. Additionally, the crushing by pressing was optimized using microwaves. The innovative application for the pellet feed operation increased the specific surface area with microwave exposure due to micro-cracking and drying of the minerals. Optical and scanning microscopy were used in this characterization. Therefore, holistic the study contributed to an innovation in the process route with the use of microwave technology controlling the humidity, increasing the efficiency in pressing and drying the iron ore.